Meningkatkan Kualitas Pembelajaran Melalui Strategi Supervisi Pendidikan di SMAN 1 Sangatta Utara - Iswanto; Siti Maryam; Fitriah Amina (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2022)
SMAN 1 Sangatta Utara faces several challenges in enhancing its educational quality, including teacher competency in implementing student-centered learning, technology integration, teacher communication and collaboration, and effective monitoring and evaluation of learning processes. To address these challenges, the school has implemented educational supervision strategies. This study investigates the effectiveness of these strategies in improving learning quality. Data was collected through in-depth structured interviews with the school principal, supervisors, teachers, and students. Classroom observations were conducted to examine the implementation of supervision strategies. The findings indicate that the supervision strategies comprise two components: planning and implementation. The implementation of these strategies has demonstrated positive impacts on learning quality, as evidenced by indicators such as improved teacher competency, technology integration, teacher communication and collaboration, and student learning outcomes. However, some limitations remain, such as insufficient time and resources for supervision activities.